Electromechanical characterizations of PEDOT:PSS and its nanocomposite thin films on a cost-effective polymer substrate for microelectromechanical systems (MEMS) applications - Shehroze Tahir Khan; Murtuza Mehdi; Tariq Jamil (eXPRESS Polymer Letters)
Conductive polymer poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) PEDOT:PSS is the most widely used material in stretchable and flexible electronics not only due to its good electrical and mechanical properties but also its use in numerous biomedical sensing applications. This article investigates the electromechanical behavior of PEDOT:PSS and its nanocomposite thin film. The films were rod-coated on a chemically treated, cost-effective single-component polymer that was previously characterized as an alternative available substrate material for stretchable and flexible microelectromechanical systems (MEMS) based devices. The results show that the films exhibit stable resistive behavior in response to various applied mechanical loads such as stretching, twisting, combined stretching, and twisting and forced vibrations. The films also show good thermal stability at relatively high temperatures. The prepared films also reveal their applicability as thermal actuators. It was also found that adding nanophases of silver material in PEDOT:PSS enhances the performance of thin films. These results also suggest that the rod-coated PEDOT:PSS and its composite thin films may have versatile applications like stretchable, twistable, and vibration-tolerant conductors, thermal actuators, and devices for future low-cost MEMS devices.